Functions, Can you solve this?

Algebra Level 5

f ( m + 1 ) = ( 1 ) m + 1 m 2 f ( m ) \large f(m+1) = (-1)^{m+1} m - 2f(m)

Let function f f , true for integers m m , satisfy the above equation and f ( 1 ) = f ( 2009 ) f(1) = f(2009) . If k = 1 2008 f ( k ) = Φ \displaystyle \sum_{k=1}^{2008} f(k) = \Phi , find 3 Φ 3 \Phi .


The answer is -1004.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Moaz Mahmud
Apr 15, 2017

Φ = k = 1 2008 f ( k ) \Phi = \displaystyle \sum_{k=1}^{2008} f(k)

= k = 1 2008 { ( 1 ) k ( k 1 ) 2 f ( k 1 ) } = \displaystyle\sum\limits_{k = 1}^{2008} \{(-1)^{k} (k-1) - 2f(k-1)\}

= k = 1 2008 ( 1 ) k ( k 1 ) 2 k = 1 2008 f ( k 1 ) = \displaystyle\sum\limits_{k = 1}^{2008} (-1)^{k} (k-1) - 2\displaystyle\sum\limits_{k = 1}^{2008} f(k-1)

= k = 0 2007 ( 1 ) k + 1 k 2 k = 0 2007 f ( k ) = \displaystyle\sum\limits_{k = 0}^{2007} (-1)^{k+1}k - 2\displaystyle\sum\limits_{k = 0}^{2007} f(k)

= 1004 2 [ f ( 0 ) + k = 1 2008 f ( k ) f ( 2008 ) ] = 1004 - 2[f(0)+\displaystyle\sum\limits_{k = 1}^{2008} f(k)-f(2008)]

= 1004 2 f ( 0 ) 2 Φ + 2 f ( 2008 ) = 1004 - 2f(0)-2\Phi+2f(2008)

3 Φ = 1004 2 f ( 0 ) + 2 f ( 2008 ) \therefore 3\Phi = 1004 - 2f(0)+2f(2008)

Now, f ( 2009 ) = ( 1 ) 2009 × 2008 2 f ( 2008 ) = f ( 1 ) = ( 1 ) 1 × 0 2 f ( 0 ) f(2009) = (-1)^{2009}\times 2008 - 2f(2008) = f(1) = (-1)^{1}\times 0 - 2f(0)

2 f ( 0 ) + 2 f ( 2008 ) = 2008 \therefore -2f(0)+2f(2008) = -2008

3 Φ = 1004 2008 = 1004 \therefore 3\Phi = 1004 - 2008 = -1004

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...